Public finance in a democratic society : The foundations of taxation and expenditure, vol 3 - Musgrave, Richard A. (Cheltenham : Edward Elgar, 2000)
In this third volume of essays by Richard Musgrave, he takes a broad view of fiscal institutions, their nature and their functions. Traditions of fiscal theory and their impact on the author's work are discussed and their linkage to theories of the state and of distributive justice are examined
Includes bibliographical references and index.
oif 15/07/14
Loan
Keywords: Fiscal policy; Tax and expenditure limitations; Intergovernmental fiscal relations; Intergovernmental tax relations